PREDIKSI EROSI PADA BEBERAPA TIPE AGROEKOSISTEM DI SUB‐DAS SERANG HULU DAERAH TANGKAPAN WADUK KEDUNG OMBO JAWA TENGAH - Jaka Suyana (Faculty of Agriculture, Universitas Sebelas Maret, 2008)
Erosion Prediction on the Agroecosystem Types at Serang Hulu Sub‐Watershed Catchment Area Kedung Ombo Reservoir in Central Java. The research about erosion prediction on the agroecosystem types at Serang Hulu Sub‐Watershed catchment area Kedung Ombo reservoir in Central Java. The results showed that rain fall were classified slightly low‐high (1276‐2970 mm/year), rain erosivity index (R) 1546‐3894. The highest soil erosion value on the agroecosystem type of inhabitants forest is 166,56‐264,83 ton/ha/year. The lowest erosion value on the agroecosystem type irrigated paddy‐soil (1,74‐11,83 ton/ha/year), followed by rainfed field (7,28 ton/ha/year), forest protect (14,29 ton/ha/year), production forest (20,90 ton/ha/year), agroforestry (56,31 ton/ha/year), dryland ( 77,86 ton/ha/year), and mixed garden(134,34‐155,49 ton/ha/year). The efforts of soil and water conservation technique must be conducted especially for the agroecosystem inhabitants forest, mixed garden, dryland, and agroforestry to stabilize and sustainablize land productivity. Keywords: Agroecosystem, Erosion, Serang Hulu Sub‐Watershed